2022
DOI: 10.1155/2022/7816333
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Physicomechanical Properties of an Active Film Based on Potato Starch, Silver Nanoparticles, and Rose Apple (Syzygium samarangense) Extract

Abstract: In the current research work, active films were made from potato starch (PS) and AgNP solution comprising of silver nanoparticles (AgNPs) and rose apple extract (RE) via the casting method at various concentrations. AgNP solution in the PS matrix significantly altered the physical properties such as opacity, water vapor permeability mechanical property, solubility, and swelling index of the films. The influence of AgNP solution on the properties of the films was deeply examined. The results found that the 15% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It was found that the moisture content was diminished by the addition of TiO2 in the CST film, which could be explained by the hydrogen bonds between TiO2 nanoparticles and matrix reduced the hydrophilic sites in starch, limiting the interaction among the starch and moisture [15]. Whereas, the enhanced moisture content of the CSRE and CSTRE film were mainly owing to the hydrophilicity of RE [16].…”
Section: Physical Appearance Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the moisture content was diminished by the addition of TiO2 in the CST film, which could be explained by the hydrogen bonds between TiO2 nanoparticles and matrix reduced the hydrophilic sites in starch, limiting the interaction among the starch and moisture [15]. Whereas, the enhanced moisture content of the CSRE and CSTRE film were mainly owing to the hydrophilicity of RE [16].…”
Section: Physical Appearance Propertiesmentioning
confidence: 99%
“…As presented in Table 1, the films were evidently thickened as the incorporation of TiO2 nanoparticles and RE had negligible impact on the film thickness. It could be related to the addition of TiO2 enhanced solid mass in the film's network, with the aggregation of small nanoparticles in the starch matrix, which promoted the film thickness [15].…”
Section: Physical Appearance Propertiesmentioning
confidence: 99%
“…e peaks between 850 and 1200 cm −1 link with glucose pyranose and C-O vibrations stretching glucose units, coupling bonds (-C-O and C-C) stretching, respectively [23,24]. e peaks noticed within a range of 850-1450 cm −1 represent C-OH stretching vibration and O-H bond vibration [25,26]. As ME and GA were incorporated, the positions of peaks slightly altered and shifted to lower wave numbers, possibly due to some interaction among active lm components (MS, GA, and ME) [27].…”
Section: Ftir Analysis Ftir Spectra (S) Of the Ms-based Filmsmentioning
confidence: 99%
“…Food packaging films protect food from microbial contamination during storage and reduce the risk of foodborne illnesses, such as food poisoning, from consuming contaminated foods. [1,2] These films also preserve the food's quality and increase the food's shelf life. [3] For instance, antimicrobial food packaging films can inhibit the growth of microorganisms by releasing bioactive chemicals in a regulated manner.…”
Section: Introductionmentioning
confidence: 99%